Architectural Research as On-Going Group Collaboration - Koester, Robert J. (ARCC Conference Repository, 2019)
Clarifying the frameworks for the conduct of architectural research can liberate educators and practitioners alike. This paper accepts the premise that modes of research are themselves forms of social communication and that knowledge emerges as a social construct. The publication of work and its presentation in a social setting reinforces the fact that it is only by agreement within the peer group that the new theories are tested, new understandings evaluated, and knowledge legitimized. Two modes of research are now widely accepted. Mode I research, regarded as the Royal Mode of research, involves the formalized framing of a hypothesis and its testing for proof; Mode II, labeled by some as the Nomad Mode, is transient and highly dependent on context”it is trans-disciplinary, non-hierarchical, and involves many actors. Of the two, Mode II research functions as the research model of significant fit for the architectural community”it obviates competitive peer pressure and instead leverages the role of peers as participants in on-going group collaboration.